2015
DOI: 10.1021/acsnano.5b04420
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Toxicity Ranking for Metal Oxide Nanoparticles via an in Vitro Dosimetry Model

Abstract: It has been argued that in vitro toxicity testing of engineered nanoparticles (NPs) should consider delivered dose (i.e., NP mass settled per suspension volume) rather than relying exclusively on administered dose (initial NP mass concentration). Delivered dose calculations require quantification of NP sedimentation in tissue cell culture media, taking into consideration fundamental suspension properties. In this article, we calculate delivered dose using a first-principles "particles in a box" sedimentation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 66 publications
0
57
0
Order By: Relevance
“…This dose range is equivalent to 0.5-6 mg/m 2 of MOx exposure in the mouse lung, assuming the alveolar epithelium surface area of 0.05 m 2 and a body weight of 25 g [38]. Assuming that the in vitro MOx dose is homogeneously distributed in cell culture media (100 μL/well, 96 well plate) and the percentages of MOx settlement are higher than 70% [39], the in vitro cell exposure dose would be 1.6-16 μg/mL. The in vivo dose used in this study is 2 mg/kg, which has previously been shown to be on the steep part of the dose response curve for MOx and relevant to the airborne levels of MOx in workplace [13].…”
Section: Discussionmentioning
confidence: 99%
“…This dose range is equivalent to 0.5-6 mg/m 2 of MOx exposure in the mouse lung, assuming the alveolar epithelium surface area of 0.05 m 2 and a body weight of 25 g [38]. Assuming that the in vitro MOx dose is homogeneously distributed in cell culture media (100 μL/well, 96 well plate) and the percentages of MOx settlement are higher than 70% [39], the in vitro cell exposure dose would be 1.6-16 μg/mL. The in vivo dose used in this study is 2 mg/kg, which has previously been shown to be on the steep part of the dose response curve for MOx and relevant to the airborne levels of MOx in workplace [13].…”
Section: Discussionmentioning
confidence: 99%
“…The density of surface silanols can also be a determinant of electrostatic interaction of fumed SiNPs with membrane phospholipids (Zhang et al, 2012). Recent reports highlight the importance of characterizing nanoparticle interactions in liquid suspensions and their impact on in vitro dosimetry, along with determining sedimentation and diffusion rates of suspended nanoparticle agglomerates and nonagglomerated particles to improve estimates of dose delivered to cells (Cohen et al, 2013;DeLoid et al, 2014;Liu et al, 2015;Pal et al, 2015). Correction of the b potency estimates for the effective delivered dose of the SiNPs in the present study indicated a 64% (1.64Â) increase in deposited dose of SiNP (12 nm) relative to the other SiNPs.…”
Section: Discussionmentioning
confidence: 99%
“…[18] The resulting water-soluble ZnO NCs exhibited unprecedentedu ltralong-lived electron-hole separation (up to 2.2 ms) [18a] and, by taking advantage of the exceptional properties of ZnO NCs modifiedw ith ao ligoethylene glycol carboxylate shell, we created an anohybrid system for H 2 evolution under visible-light irradiation. [21] Following the statement of Cohen and co-workers: [22] "efforts are now mounting to ensure the development and application of safe-by-design engineered nanomaterials so as to avoid adverse environmental and humanh ealth impacts" and advancing the OSSOM method, herein we report on the synthesis of quantum-sized ZnO NCs coated by ad enselyp acked 2-(2-methoxyethoxy)acetate ligand shell as am odel system for in vitro cytotoxicity studies by cell metabolic activity assay (MTT) in normal( MRC-5) and cancer( A549) human lung cell lines. reported another variant of the organometallic approach for ZnO NC synthesis through the hydrolysis of R 2 Zn supported by substoichiometric quantities of zinc carboxylates Zn(O 2 CR') 2 or zinc phoshinatesZ n(O 2 PR' 2 ) 2 and their utility as ac omponent of ZnO/Cu nanocatalysts or antimicrobial polymer surfaces.…”
Section: Introductionmentioning
confidence: 99%